Acoustic vibration induced high electromagnetic responses of Fe3O4 nano-hollow spheres in the THz regime. (18th May 2015) - Rakshit, Rupali; Sarkar, Debasish; Pal, Monalisa; Serite, Kazunori; Tonouchi, Masayoshi; Mandal, Kalyan
Abstract: Herein, we investigate the origin of enhanced absorption and complex conductivity of magnetite (Fe3 O4 ) nano-hollow spheres (NHSs) in contrast to its nanoparticles (NPs) configuration in the frequency range 0.4–2.0 THz. The maximum absorption for NHSs and NPs of the same average diameter (~100 nm) are found to be 246.27 and 48.35 cm −1 at 1.8 THz, respectively. A detailed study suggests that the multiple resonance peaks in the absorption spectra are due to low frequency acoustic vibrational phonon modes of Fe3 O4 nanostructures. Moreover, we demonstrate that the magnitude of total absorption can be tailored by varying the shell thickness of NHSs. It is found to increase with increasing shell thickness, and attain a maximum value of 498.5 cm −1 for the NHSs of average diameter 350 nm at 1.8 THz. The invariance of frequency dependent magnetic permeability points out that the absorption is basically due to dielectric loss instead of magnetic loss. The enhanced THz conductivity of Fe3 O4 NHSs, as compared to NPs is described in light of thermally activated polaronic hopping which is found to increase with increasing THz absorption. Finally, the size dependent THz conductivity of NHSs confirms its sole dependence on the magnitude of THz absorptivity.